Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Make a Match di SD - Nindy Puspita Yudha; Nasrul Nasrul (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to describe the improvement of integrated thematic learning process  using the Cooperative type Make A Match model in class IV SDN 19 ATTS  Bukittinggi  . The type of this research is Classroom Action Research (PTK) using a qualitative and quantitative approach. The results of research showed the increasing on: a) the score oh the lesson plan in cycle I was 91.25% (SB), cycle II 97,5% (SB); b) aspect observation of teacher cycle I 81.25% (B), cycle II 92,5% (SB); c) aspects  observation of student cycle I students 81,25% (B) and the second cycle II 92,5% (SB). So, Cooperative Learning Type Make a Match Model  can improve student learning process in integrated thematic learning.